2020
DOI: 10.1177/1362361320929453
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the writing skills of autistic and nonautistic university students: A collaboration with autistic university students

Abstract: The writing skills of autistic university students have received very little empirical attention. Previous research has suggested that autistic people may struggle with writing, in part, due to challenges with Theory of Mind. However, other research indicates that Theory of Mind difficulties are far from universal in autism, varying across developmental and social contexts. Through a participatory research approach, autistic university students contributed to the current study examining the writing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 84 publications
(108 reference statements)
0
19
0
Order By: Relevance
“…For example, Lei and Russell (2021) interviewed 18 autistic and 18 non-autistic students from the United Kingdom about perceptions of their self-determination (their ability to determine their own future and experiences) at university, noting that while there were commonalities, autistic students discussed autistic-specific strengths and more difficulties with transitions. Gillespie-Lynch et al (2020) compared the writing skills of 25 autistic and 25 non-autistic students in the United States, finding autistic students expressed more writing skill and quality, higher nonverbal intelligence, and more perfectionist attitudes toward writing. These studies indicate there are unique strengths and challenges experienced by autistic students and comparing could help us to identify autistic-specific support versus support that would benefit students more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lei and Russell (2021) interviewed 18 autistic and 18 non-autistic students from the United Kingdom about perceptions of their self-determination (their ability to determine their own future and experiences) at university, noting that while there were commonalities, autistic students discussed autistic-specific strengths and more difficulties with transitions. Gillespie-Lynch et al (2020) compared the writing skills of 25 autistic and 25 non-autistic students in the United States, finding autistic students expressed more writing skill and quality, higher nonverbal intelligence, and more perfectionist attitudes toward writing. These studies indicate there are unique strengths and challenges experienced by autistic students and comparing could help us to identify autistic-specific support versus support that would benefit students more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Many autistic people are able to recognize details that may remain hidden to “neurotypical” individuals (e.g., Dakin and Frith, 2005 ; Lorenz and Heinitz, 2014 ). Autistic university students also exhibited enhanced writing skills relative to their non-autistic peers at one university ( Gillespie-Lynch et al, 2020 ). Similar patterns have been observed in more generalizable samples: incoming autistic university students in the Netherlands outperformed their peers on the Dutch Language Proficiency Test ( Bakker et al, 2019 ), as did autistic students in the United States on the verbal SAT ( Fernandes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the medium term, we plan to adapt the system to support other guides than Battelle's and to deepen the existing knowledge about technology-aided interventions to improve pre-writing skills when necessary. In addition, we want to focus on the specific challenges faced by children affected by autism spectrum disorders, taking into account the findings of Gillespie-Lynch et al [26] in more advances stages of education. Through a study conducted with a sample of autistic and non-autistic university students, these authors found that some of the autistic students had more advanced writing skills than their non-autistic peers (mostly attributable to higher non-verbal intelligence).…”
Section: Discussionmentioning
confidence: 99%